“Modal Preludes and Fugues in C” by Borislava Stronko: Specific Use of Modal Technology: ДО 50-РІЧЧЯ КОМПОЗИТОРА - Postovoitova, Svetlana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
The relevance of the article. The most pressing need today is to turn to modern samples of polyphonic music, which is due, on the one hand, to artistic practice, and on the other, to rethinking traditional polyphonic forms and techniques in the context of a total experiment and a radical renewal of musical techniques. B. Stronko’s “Modal Preludes and Fugues in C” demonstrate a completely new, author’s version of the interpretation of the polyphonic cycle, which is due to the non-traditional combination of modality with polyphonic principles and methods of development. The change in the functionally centralized fret-tonal system to a radically different, modal, type of modal organization caused significant changes at all tiers of the multilevel organization of the fugue, starting from its core — the theme, ending with the principles of composition and shaping. To trace exactly what specific changes that were caused by the use of modal technique in the framework of the fugue and is the central problem of the study and determines its relevance Scientific novelty: for the first time, all the preludes and fugues of the cycle “Modal preludes and fugues in C” were thoroughly analyzed with an emphasis on the study of the “semantic source” of the polyphonic cycle (fugue), its quintessence (theme) in terms of the influence of the principles of modality on the construction of the fugue. The purpose of the article: to identify the features of the use of modal technique and the specificity of its influence on various structural levels of the fugue in the cycle “Modal preludes and fugues in C” by Boryslav Stronkо, as well as to determine the special features of the composer’s polyphonic thinking. The research methodology includes the use of systemic and functional methods. Main results and conclusions. All fugues from the cycle «Modal Preludes and Fugues in C» by B. Stronko represent an open cycle based on the modal principle of organization. The cycle itself is potentially open and represents the composer’s desire to achieve freedom and emphasize the potential for infinity of the process of creating modes. Each pair of preludes and fugues is limited by a scale of a certain design, which made it possible to create compositions with a pronounced individual flavor. At the level of thematicism: compactness of themes and fugues themselves, intonation specificity, depending on the structure of the fret. With further themes, linearity of development prevails, the composer uses the principle of multivariate repetition (isomelia, isorhythmy, interpolation, combinatorics), which has a certain relationship with rehearsal technique and becomes a specific feature of Boryslav Stronko’s polyphonic thinking. Multivariate repetition of the material, despite the actual changes, enhances the fading effect, being in one place and organically combines with the idea of being in the conditions of one specific sound of the chosen fret. Attention is drawn to the technique of replicating rhythmic-intonational structures — it is a quasi-sequential repetition of a motive in one or several voices at the same time, most often it variably changes in all voices, repeating with a horizontal shift or with the simultaneous use of various techniques (isorhythmy, isomelia, combinatorics). The role of ostinato increases significantly, which, together with the above techniques, contributes to the creation of the effect of hidden internal movement while actually staying in one place. It should be noted that all the above principles, which create the effect of a specific sound and work on the idea of constant rotation in a single sound space, turn out to be stable not only for “Modal preludes and fugues in C”, but also for other works of the composer: “Labyrinth Chord”, 4-part symphony for virtual ensemble (2016), “Time Crystals” (or “Metavariations for metapiano”) is an electronic music cycle (2018).